Stigmasterol Simultaneously Induces Apoptosis and Protective Autophagy by Inhibiting Akt/mTOR Pathway in Gastric Cancer Cells - Zhao, Huange; Zhang, Xian; Wang, Min; Lin, Yingying; Zhou, Songlin (Frontiers in Oncology, 2021)
Background: Stigmasterol (SS) has been proven to possess potential anticancer activities in several cancer cell lines, but its molecular mechanism is still unknown. Thus, we investigated whether SS has the capabilities of inducing autophagy and its molecular mechanisms in gastric cancer cells. Methods: We used CCK8 assay, clone formation assay and EdU proliferation assay to assess the effects of SS on cell proliferation in SGC-7901 and MGC-803 cells in vitro, and its inhibition on the tumor growth of gastric cancer was observed in vivo. Apoptosis induced by SS was demonstrated using Hoechst and TUNEL staining, Annexin V-FITC/PI assay. Immunofluorescence staining is used to detect the formation of autophagosomes triggered by SS. Apoptosis and autophagy related proteins were analyzed by western blot. Results: The results indicated that SS treatment inhibited cell proliferation in SGC-7901 and MGC-803 cells. Furthermore, SS treatment induced apoptosis and autophagy by blocking Akt/mTOR signaling pathway. The pretreatment with the Akt inhibitor MK-2206 could promote apoptosis and autophagy induced by SS, predicting that Akt/mTOR pathway is involved in SS-induced apoptosis and autophagy. In addition, blockade of autophagy with 3-MA (an inhibitor of autophagy) enhanced SS-induced apoptosis in SGC-7901 and MGC-803 cells, implying that autophagy mediated by SS plays a cytoprotective role against apoptosis. Finally, an in vivo study demonstrated that tumor growth of gastric cancer was suppressed by SS in a xenograft model. Conclusion: Our findings illustrated that SS simultaneously induces apoptosis and protective autophagy by inhibiting Akt/mTOR pathway in gastric cancer cells at the first time. More importently, our work indicated that SS combined with autophagy inhibitor could be a promising therapy for gastric cancer.